Under Thirty. (Wien : Galerie Metropol, 1993)
Kargl, Georg ; King, Ashley ; Viscio, Alex ; Collishaw, Mat ; Dion, Mark ; Oppenheim, Kristin ; Tiravanija, Rirkrit ; Kustera, Carter ; Jermini, Stefano ; Durward, Gram ; Pearlstein, Alix ; Joo, Michael ; Peyton, Elizabeth ; Lidrbauch, Christine ; Anderson, Angela ; Brown, Gavin ; Armleder, John ; Flurry, Sylvie ; Lekay, John ; King, Ashley ; Bernard, John Saint ; Krystufek, Elke ; Tower, Jon ; Ganahl, Rainer ; Landers, Kevin ; Goldsmith, Kenith ; Lekay, John
Under Thirty, Galerie Metropol, Wien, February 1993
kunstcatalogus